2017
DOI: 10.1007/s11695-017-2894-0
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Functioning in Mid-life Treatment-Seeking Adults with Obesity: a Cross-sectional Study

Abstract: Findings support the contribution of obesity to selective aspects of mid-life cognition after controlling for obesity-related comorbidities, while addressing limitations of previous research including employment of an adequate sample, a healthy-weight control group and stringent exclusion criteria. Further investigation into the functional impact of such deficits, the mechanisms underlying these poorer cognitive outcomes and the impact of weight-loss on cognition is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 47 publications
0
15
1
Order By: Relevance
“…Global performance for inhibitory control was similar for all groups in our sample, as measured by the Go/no-Go subtest from the TAP, and for flexibility as measured with the flexibility subtest from the same battery. Contrary to previous findings [29,30,[59][60][61], inhibitory control and mental flexibility capacities were similar regardless of weight status. In addition, the number of commission errors, omission errors and reaction times in the modified Affective Shifting Task revealed no significant differences according to weight status when participants were not primed with a non-attentively perceived food cue.…”
Section: Global Performancecontrasting
confidence: 99%
“…Global performance for inhibitory control was similar for all groups in our sample, as measured by the Go/no-Go subtest from the TAP, and for flexibility as measured with the flexibility subtest from the same battery. Contrary to previous findings [29,30,[59][60][61], inhibitory control and mental flexibility capacities were similar regardless of weight status. In addition, the number of commission errors, omission errors and reaction times in the modified Affective Shifting Task revealed no significant differences according to weight status when participants were not primed with a non-attentively perceived food cue.…”
Section: Global Performancecontrasting
confidence: 99%
“…A converging body of work implicates excess adiposity as a contributing factor to poorer cognitive function across the lifespan . However, the identification of dietary factors with the potential to provide neuroprotection among populations with elevated weight status has been limited.…”
Section: Discussionmentioning
confidence: 99%
“…Defined as having a body mass index (BMI; kg m −2 ) greater than 25.0, individuals with overweight and obesity are at higher risk of exhibiting deficits in cognition, particularly executive function, than their healthy weight peers . Intriguingly, these deficits in cognitive function amongst individuals with overweight and obesity have been observed independently of obesity's clinical consequences such as type 2 diabetes, alterations in glycemic control, and metabolic risk factors . Thus, the introduction of lutein and zeaxanthin into diet may serve as a relatively cost‐effective approach to preventing, or delaying, cognitive impairments due to increased adiposity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…;Prickett, Stolwyk, O'Brien, & Brennan, 2018), although not all studies have found this relationship (for reviews seeHiggs & Spetter, 2018;Loprinzi & Frith, 2018;Prickett, Brennan, & Stolwyk, 2015). Neuroimaging studies also point to structural deficits and damage to memory associated areas being associated with overweight and obesity.…”
mentioning
confidence: 99%